Systematic Review of Dry Socket - Rashidnezhad, Amin; Jikia, Maia (Caucasus Journal of Health Sciences and Public Health, 2020)
Dry socket, also termed fibrinolytic osteitis or alveolar osteitis, most common postsurgical complication following extraction of impacted molar teeth. A dry socket lesion is a post-extraction socket that exhibits exposed bone that is not covered by a blood clot or healing epithelium and exists inside or around the perimeter of the socket or alveolus for days after the extraction procedure. A great body of literature is devoted to alveolar osteitis addressing the etiology and pathophysiology of this condition. In addition, numerous studies are available discussing methods and techniques to prevent this condition. this is a systematic review, which shows a compendious review about the etiology, prevention and management of Alveolar Osteitis. The risk factors are smoking, surgical trauma, flap design, single extractions, age, medical history, systemic disorder, extraction site, difficulty of the surgery and the previous surgical site infection. The prevention methods include avoiding smoking before and after surgery and a traumatic surgery, the use of antibiotics, such as, azithromycin, can be considered, the other preventive measures such as chlorhexidine rinse or gel can be effective in the reduction of dry socket incidence. Over the years little progress has been made in establishing firm conclusions as to how best dry socket should be managed.